Extraction parameters of essential oil of coffee with the use of CO2 supercritical - Silva, Luciano Luiz; Fernandes, Suellen Cadorin; Costelli, Murilo Cesar; Savio, Juliana; Lopes, Toni Jefferson; Besegatto, Stefane Vieira; Capelezzo, Ana Paula (Coffee Science - ISSN 1984-3909, 2015)
The production and consumption of coffee in Brazil comes in an increasing considerably in recent years, accounting for 33.60% of world production. Roasted coffee contains high amounts of volatiles which provide their characteristic flavor and aroma, which are found mainly in their oil. Already, the oil obtained from green coffee is a material rich in unsaponifiables compounds and sterols. Facing the technologies used for the extraction of essential oils, the supercritical technology emerges as a clean and free of organic solvent remnant technique, when using supercritical CO2 as solvent, which presents characteristics: non-toxic, non-flammable and relatively low cost. Through the extraction kinetics (50ºC and 220 bar) it was possible to determine the extraction time of 3h 30 min for roasted and green coffee. By means of the Statistica 6.0® software, it was found that only the pressure variable had significant influence on the yield of extraction with supercritical CO2 for roasted coffee. For green coffee, it was found that none of the parameters was significant. The yield obtained for green and roasted coffee were 3.68 and 7.52%, respectively.